The Deformation of rigid pavement at an early age: Deformation of rigid pavement at an early age - Maharduta, Diego Maradona; Niken, Chatarina; Widyawati, Ratna (REKAYASA: Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2024)
Cracks in rigid pavements are common. One of the causes is cracking caused by shrinkage that the concrete is unable to accommodate. When early age shrinkage cannot be accommodated, the risk of performance degradation becomes greater. The purpose of this study is to determine the deformation that occurs on concrete roads in Lampung Province, Indonesia from the time of casting until the concrete is 24 hours old. The research sample is a rigid pavement measuring 5000×4500×300 mm with fs' 4.5 MPa and f "c 25 Mpa which is a real toll road. Curing of concrete is done by covering the concrete with geotextile and moistened every 2 hours since the concrete is 13 hours 30 minutes old. The research methods used are observation and interview. The tool used in the research is Vibration Wired Embedded Strain Gauge (VWESG) and the research was conducted for 24 hours since the concrete was cast. Data analysis in this study uses descriptive analysis of observation and measurement results. The results showed that the deformation of concrete that occurs in rigid pavements in Indonesia from the largest to the smallest in order starting from the middle part, the long side, the short side, then the corner of the segment.